Effects of a magnetic field and initial stress on reflection of SV-waves at a free surface with voids under gravity - Anya Augustine Igwebuike; Akhtar M.W.; Abo-Dahab Syed Muhammad; Kaneez Hajra; Khan Aftab; Jahangir Adnan (Journal of the Mechanical Behavior of Materials, 2018)
The present study deals with the reflection of SV-waves at a free surface in the presence of magnetic field, initial stress, voids and gravity. When an SV-wave incident on the free surface of an elastic half space, two damped P-waves and an SV-wave are reflected. Among these waves, P-waves are only affected by magnetic fields whereas SV-waves are influenced by both, initial stress and magnetic fields. Effect of gravity is negligible whereas voids played a significant role. These observations can be helpful for seismology and earthquake sciences.